Fetal echocardiographic prediction score for perinatal mortality in tricuspid valve dysplasia and Ebstein's anomaly. (3rd February 2020) - Torigoe, F.; Ishida, H.; Ishii, Y.; Ishii, R.; Narita, J.; Kawazu, Y.; Kayatani, F.; Inamura, N.
ABSTRACT: Objectives: Tricuspid valve dysplasia (TVD) and Ebstein's anomaly (EA) diagnosed by fetal echocardiography vary greatly in terms of clinical severity and prognosis. The Celermajer index and Simpson–Andrews–Sharland (SAS) score have been reported previously for the prediction of prognosis in cases of TVD/EA; however, they do not take into account the hemodynamic impact of left ventricular (LV) function, which has recently been implicated as being important in the pathophysiology of TVD/EA. The aim of this study was to develop a novel scoring system that includes LV function for the prediction of perinatal death in fetuses diagnosed with TVD/EA. Methods: The clinical records of 36 fetuses diagnosed prenatally with TVD/EA between 2000 and 2015 in our hospital were reviewed. Univariate analysis was used to assess the association between perinatal death (defined as death between 22 weeks' gestation and 4 weeks after delivery) and gestational age at diagnosis, cardiothoracic area ratio (CTAR), degree of pulmonary artery flow, direction of ductal flow, right‐to‐left ventricular diameter ratio, tricuspid regurgitation (TR) maximum velocity, Celermajer index, SAS score and LV‐Tei index. A new prognostic score, the TRIPP score (TRIcuspid malformation Prognosis Prediction score), was developed using the parameters found to be associated significantly with perinatal death. The predictive value of this score was assessed in an additional nine fetuses diagnosed with TVD/EA. Results: Thirty‐six fetuses were diagnosed prenatally with TVD/EA, two of which were terminated, one was lost to follow‐up and two died before 22 weeks' gestation. Of the 31 included fetuses, 10 (32%) died in the perinatal period. Univariate analysis demonstrated that TR maximum velocity was significantly lower (2.22 ± 0.17 m/s vs 3.26 ± 0.12 m/s; P  < 0.001) and SAS score was significantly higher (5.7 ± 0.6 points vs 2.8 ± 0.4 points; P  = 0.0014) in cases of perinatal death than in surviving fetuses. The degree of pulmonary artery flow and the direction of ductal flow were also associated significantly with perinatal death ( P  < 0.01 for both). Notably, LV‐Tei index was significantly higher in cases of perinatal death than in surviving fetuses (0.81 ± 0.08 vs 0.50 ± 0.05; P  < 0.001). In contrast, there was no significant difference in Celermajer index, CTAR or right‐to‐left ventricular diameter ratio. Finally, we established a novel combinatorial scoring system, the TRIPP score, including the four significant factors: TR maximum velocity, pulmonary artery flow, direction of ductal flow and LV‐Tei index. The TRIPP score was found to predict efficiently perinatal mortality in fetuses with TVD/EA. Conclusions: Our novel combinatorial score of echocardiographic parameters, the TRIPP score, including LV‐Tei index, is easy to measure and provides a good tool for the prediction of perinatal mortality in fetuses diagnosed prenatally with TVD/EA. Copyright © 2019 ISUOG. Published by John Wiley & Sons Ltd.